MELIDIK KONEKSI IPK DAN KEMAMPUAN BERBAHASA INDONESIA MAHASISWA SEMESTER III KELAS A PROGRA STUDI PENIDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNDANA KUPANG - Hayon G. Nico; Firmina Angela Nai; Fransiskus Sanda (Jurnal Lazuardi, 2020)
The Head of the Central Language Agency said that Indonesian has now become an international language. Since the 3rd Oath, namely Speaking One Indonesian Language which was made by the youth on October 28, 1928, speaking Indonesian is still one of the bonds that binds a sense of brotherhood among the citizens of the Unitary Republic of Indonesia hereby. day. The question is: is pride only limited to Indonesian as a tool to unite the nation? Indonesian is still the national language. Indonesian has become an international language? The answer is: Not yet. For students of the Indonesian Language and Literature Study Program, FKIP Undana, a sense of pride or a sense of belonging and until now they still use the Indonesian language as a means of communication and the various roles and functions of the Indonesian language as above are not enough. His students are prospective teachers of Indonesian Language subjects from SMP, SMA and SMK levels. As a prospective teacher, the ability and skills to speak Indonesian properly and correctly do not only underline the role of the citizens of the Republic of Indonesia. Students who will become teachers of Indonesian Language Subjects also have a noble role and duty, namely to educate the nation's life through Indonesian. The 2013 curriculum or what is known as the National Curriculum, has renovated Indonesian language learning from partial learning of Listening, Speaking, Reading, and Writing, to becoming text-based integrative learning.